Artist Fellow Dr. Migline Paroumanou and Prof. Dr. Ute Fendler talk about art, ritual and healing after colonialism - Paroumanou, Migline; Fendler, Ute (Cluster Conversations, 2026)
This latest episode of the Cluster Conversatioins features Prof. Dr. Ute Fendler and artist Migline Paroumanou reflecting on her work during a residency in Bayreuth, where she explores identity, memory and belonging through the historical context of La Réunion, the Indian Ocean and Africa. Drawing on colonial history, slavery and ritual practices, she describes her artistic approach as a symbolic act of repair and healing that connects past trauma with present human experience. Through ceramics, performance and collective participation, her practice invites others to engage consciously in processes of apology, care and transformation.